The Difficulties and prerequisites of intellectualizing the Filipino language in the field of science - Joven, Celestino Cesar D. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1993)
Language intellectualization is the technicalization of language necessitated by the global widening consciousness. It was first described by Bohuslav Havraneck in 1932 as the expansion of lexicon in order to gain access to the massive influx of information. Modernization is the stimulus of intellectualization and because of the radical changes caused by industrialization, modernization has become one of the central preoccupation of all nations. Havraneck however did not include in his studies an investigation on Intellectualization as a process. Without which, data on what are the prerequisites of language intellectualization, what are its varieties, and what are its pros and cons are not available. So this study was focused on filling these information gaps and to correlate its findings to the intellectualization process of the Filipino language. The findings of this research were not very encouraging. It seems that the Philippines still lacks many of the prerequisites of intellectualization. And because of the further complications caused by the superposition of the English language and the residual iinfluece of the country's long history of colonization, the intellectualization of the Filipino language might indirectly worsen the western mentality of many.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.